A Multi-Temporal Remote Sensing Approach to Quantify Land Cover Change and its Impact on Ecosystem Sustainability in Riau, Indonesia - Purba, Novrian Maria; Hariyanti, Fitri; Saputra, Andriansyah Muqiit Wardoyo (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
This study analyzes land cover change in Riau Province from 2015 to 2024, focusingon deforestation and degradation as indicators of ecosystem sustainability. Landsat 8 OLI/TIRSand Landsat 9 OLI-2 imagery processed in Google Earth Engine (GEE), combined with MODIShotspot data (MOD14A1) and socioeconomic indicators—Gross Regional Domestic Product(GRDP) and Open Unemployment Rate (OUR) from Statistics Indonesia (BPS)—were used toassess spatiotemporal patterns. The Normalized Difference Vegetation Index (NDVI) wasapplied with thresholds for deforestation (NDVI < –0.3) and degradation (–0.3 ? NDVI ? –0.1).Results show that 2015 was the most severe period, dominated by peatland fires, while 2019recorded forest loss at a lower intensity and 2020–2024 indicated partial vegetation recoverylinked to restoration efforts. Pelalawan, Indragiri Hilir, and Kampar were the most affecteddistricts. Correlation analysis revealed that fire hotspots had the strongest association with landcover change, while economic and social indicators showed weaker relationships. Peatland firesremain the main driver of land degradation, emphasizing the need to strengthen fire management,peatland protection, and sustainable plantation governance to support Sustainable DevelopmentGoal (SDG) 15 on Life on Land, particularly the target of Land Degradation Neutrality (15.3.1)by 2030.